Faktor Penerimaan dan Penggunaan Siswaskeudes oleh Pengawas Keuangan Desa - Putu Widiantari; Made Gede Wirakusuma; Ni Putu Sri Harta Mimba; Putu Agus Ardiana (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2024)
This research investigates the factors influencing the acceptance and use of the Village Financial Monitoring System (Siswaskeudes) application by village financial supervisors. Utilizing an interpretive approach and hermeneutic phenomenology, the study aims to understand supervisors' experiences and perceptions regarding the usefulness and ease of use of Siswaskeudes. Data were collected through in-depth interviews with five informants from the Denpasar City Inspectorate. The findings indicate that perceived usefulness, ease of use, attitudes toward behavior, subjective norms, and perceived behavioral control are crucial in determining application usage. Most informants found Siswaskeudes to facilitate easier data access and enhance work efficiency, despite identifying initial use challenges and the need for further development. Compliance with legal regulations, reflected in subjective norms, is a primary driver of the application's use. This research recommends ongoing development, training, regular monitoring, team support, and security enhancements to boost Siswaskeudes' acceptance and usage. Future research should explore user satisfaction using quantitative approaches with the Technology Acceptance Model (TAM) and consider additional variables such as security and cost savings.